Lymphocyte Activation Gene (LAG)-3 Is Associated With Mucosal Inflammation and Disease Activity in Ulcerative Colitis. (16th March 2020) - Slevin, Stephanie M; Garner, Lucy C; Lahiff, Conor; Tan, Malcolm; Wang, Lai Mun; Ferry, Helen; Greenaway, Borgel; Lynch, Kate; Geremia, Alessandra; Hughes, Stephen; Leavens, Karen; Krull, David; et al.
Abstract: Background and Aims: Lymphocyte activation gene [LAG]-3 is an immune checkpoint and its expression identifies recently activated lymphocytes that may contribute to inflammation. We investigated the role of LAG-3 by analysing its expression and function in immune cells from blood and tissue of patients with ulcerative colitis [UC]. Methods: The phenotypic properties of LAG-3 + T cells were determined by flow cytometry, qRT-PCR and single-cell RNA-sequencing. LAG-3 + cells were quantified and correlated with disease activity. The functional effects of LAG-3 + cells were tested using a depleting anti-LAG-3 monoclonal antibody [mAb] in a mixed lymphocyte reaction [MLR]. Results: LAG-3 + cells in the blood were negligible. LAG-3 + lymphocytes were markedly increased in inflamed mucosal tissue and both frequencies of LAG-3 + T cells and transcript levels of LAG3 correlated with endoscopic severity. LAG-3 expression was predominantly on effector memory T cells, and single-cell RNA-sequencing revealed LAG3 expression in activated and cytokine-producing T cell subsets. Foxp3 + CD25 hi Tregs also expressed LAG-3, although most mucosal Tregs were LAG-3 − . Mucosal LAG-3 + cells produced mainly interferon γ [IFNγ] and interleukin-17A. LAG-3 + cell numbers decreased in patients who responded to biologics, and remained elevated in non-responders. Treatment with a depleting anti-LAG-3 mAb led to a reduction in proliferation and IFNγ production in an MLR. Conclusions: LAG-3 + cells are increased in the inflamed mucosa, predominantly on effector memory T cells with an activated phenotype and their cell numbers positively correlate with disease activity. Depleting LAG-3 eliminates activated proliferating T cells, and hence LAG-3 could be a therapeutic target in UC.